IMPLEMENTASI KEGIATAN MEWARNAI DALAM MENINGKATKAN ASPEK PERKEMBANGAN MOTORIK HALUS ANAK KELOMPOK B DI KB NURHIDAYAH TAHUN PELAJARAN 2022-2023 - Yuliana (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
Implemenentation of coloring activities in improving aspects of chlidren’s fine motor development the purpose of this research is to reveal about planning coloring activities to improve aspects of fine motor development in group B children in the Nurhidayah KB for the 2022-2023 academic year implementation of coloring activities in improving aspects fine motor development in group B children in the Nurhidayah KB For the 2022-2023 academic year evaluation of fine motor development in group B children in tthe Nurhidayah KB For the 2022-2023 Academic year this study uses a qualitative approach and a type of phenomenological approach data collection techniques using observation interviews and documentation as for the technical analysis used is data reduction display data and verification of data and dtawing conclusions the research results show that: Planning coloring activities to improve aspects of fine motor development for group B chilfren at the Nurhidayah KB for the 2022-2023 school year. Make RPPH in accordance with the guidebook for preparing assessments using a star striker. The implementation of coloring activities in imprroving aspects of childrens fine motor development in group B at the Nurhidayah KB for the 2022-2023 academic year consists of seveal steps namely the core introduction and closing evaluation. Step activities in improving aspects of group B fine motor development at Nurhidayah KB 2022-2023 aqcademic year by collecting star stickers then adjusting to aspects of fine motor development that you want to achieve.